2018
DOI: 10.1186/s12909-018-1342-8
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition and extraversion of medical students interact to predict their empathic communication perceived by simulated patients

Abstract: BackgroundThis study assessed the impact of medical students’ emotion recognition ability and extraversion on their empathic communication, as perceived by simulated patients in a training context.MethodsThis study used a crossed-effect data structure and examined 245 students in their fourth year of medical school. The students’ personality traits were assessed based on a self-assessment questionnaire of the short form of the Big Five Inventory; their emotion recognition ability was measured using a performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Extravert people, who are more focused on external world rather than emotions, and who seek contact with others [ 10 ] – are less susceptible to personal distress, as they are less concentrated on their “self”. In a study on communication between a general practitioner and a simulated patient, Extraversion and Emotion Recognition Ability, turned to be the most important factors that influenced positive assessment of the relation by patients [ 15 ]. The dimension of Openness and its subcomponents are in a positive correlation with Empathetic Concern and Perspective Taking [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extravert people, who are more focused on external world rather than emotions, and who seek contact with others [ 10 ] – are less susceptible to personal distress, as they are less concentrated on their “self”. In a study on communication between a general practitioner and a simulated patient, Extraversion and Emotion Recognition Ability, turned to be the most important factors that influenced positive assessment of the relation by patients [ 15 ]. The dimension of Openness and its subcomponents are in a positive correlation with Empathetic Concern and Perspective Taking [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students speak with standardized patients in carefully structured, but dynamic interactions. Importantly, relational influences between standardized patient and students are operational, [1][2][3] influencing student 1,3 and standardized patient performance. Neither the impact of participants' cultural backgrounds or attitudes nor their methods for overcoming their own unconscious biases are well-characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Extraversion and agreeableness are also important for interpersonal relationships (Abbiati et al 2016) and appear crucial for effective physician-patient interactions (PPIs). Schreckenbach et al (2018) found that extraversion together with high emotion recognition, but not extraversion alone, predicted positive PPIs of medical students with standardized patients (SPs). Another study showed that medical students' empathic ability was not associated with any particular personality traits (Seitz et al 2018).…”
Section: Introductionmentioning
confidence: 99%